MOLECULAR CHARACTERIZATION OF PISTILLATE LINES IN CASTOR BEAN (RICINUS COMMUNIS L.) THROUGH MOLECULAR MARKERS - A. S. SHINDE, S. B. S. TIKKA, S. ACHARYA, W. A. SHEIKH, S. R. KALASKAR, A. H. RATHOD (The Bioscan, 2015)
Genetic diversity of 13 castor genotypes of pistillate lines (S and NES) was carried out using 33 RAPD and 11 SSR markers. The average polymorphism recorded by the 33 RAPD loci was 70.25%. The mean number of polymorphic bands per primer among 13 castor genotypes was 05 and percent polymorphism ranged from 20 to 100. The dendrogram constructed using pooled RAPD loci data clearly showed that two genotypes from NES line (JP-65 and JP-83) were highly similar and different from other genotypes. The SSR analysis with 11 microsatellite markers produced 36 alleles. The average number of alleles per locus was found to be 3.2. The highest number of alleles (10) and high PIC (0.82) value was found in locus CCat002. Cluster analysis based on SSR data clearly grouped two NES genotypes (JP-65 and JP-83) in to same clusters. For genetic diversity analysis both, RAPD and SSR may be considered reliable molecular techniques.